Mouse models of pemphigus: valuable tools to investigate pathomechanisms and novel therapeutic interventions - Emtenani, Shirin; Hertl, Michael; Schmidt, Enno; Hudemann, Christoph (Frontiers in Immunology, 2023)
Autoimmune blistering diseases (AIBD) are paradigms of autoantibody-mediated organ-specific autoimmune disorders that involve skin and/ or mucous membranes. Compared to other autoimmune diseases, the pathogenicity of autoantibodies in AIBD is relatively well described. Pemphigus is a potentially lethal autoantibody driven autoimmune disorder with a strong HLA class II association. It is mainly characterized by IgG against the desmosomal adhesion molecules desmoglein 3 (Dsg3) and Dsg1. Several murine pemphigus models were developed subsequently, each allowing the analysis of a characteristic feature, such as pathogenic IgG or Dsg3-specific T or B cells. Thus, the models can be employed to preclinically evaluate potentially novel therapies. We here thoroughly summarize past and recent efforts in developing and utilizing pemphigus mouse models for pathomechanistic investigation and therapeutic interventions.